Cover Feature: Photoswitching Affinity and Mechanism of Multivalent Lectin Ligands (Chem. Eur. J. 27/2022). Issue 27 (12th April 2022) - Osswald, Uwe; Boneberg, Johannes; Wittmann, Valentin
Abstract : Photochemical cis – trans isomerization was used to switch a divalent lectin ligand between its two forms, which show contrasting binding properties to the plant lectin wheat germ agglutinin (WGA), as visualized by the yin‐yang symbol. Whereas the E isomer (obtained under irradiation with green light) is able to bridge adjacent binding sites of WGA leading to a high‐affinity chelating binding mode, the Z isomer (obtained under UV light irradiation) crosslinks two lectin molecules associated with a much lower binding affinity. More information can be found in the Research Article by V. Wittmann and co‐authors (DOI: 10.1002/chem.202200267 ).